Identification of Parasitic Contamination in Different Water Sources in Amedi District, Kurdistan Region‎ - Farhad Buzo Mikaeel; Haifaa Golek Ismael; Khalid Jabar Aziz; Adel Talib M. Al-Saeed (Zanco Journal of Pure and Applied Sciences, 2025)
Water is the primary component of the earth, essential for all known forms of life. It is a critical nutrient for maintaining homeostasis in the human body and exists in three states: liquid, solid, and gas. Ensuring drinking water remains clean, safe, and reliable is vital. Factors such as water contamination, heavy rainfall, and agricultural residues which can transfer parasites from soil to the water's surface contribute to the spread of parasitic diseases. This study focused on detecting different parasite stages in various water sources in the Amedi district of Duhok. A total of 250 water samples collected from 6 different sources including 80 samples from household tanks water, 45 samples from sewage water, 40 samples from small rivers canals, 35 samples from ponds, 25 samples from drinking municipal project and 25 samples from springs in Amedi district. For parasitological analysis, all water samples were transported in cold boxes to the Microbiology and Parasitology Laboratory at the Medical Laboratory Department of Amedi Technical Institute. The sediment from each sample was examined under a microscope to identify helminth eggs, trophozoites, and protozoa cysts. Staining was performed using Lugol's iodine and the modified Ziehl-Neelsen acid-fast method. Non-nutritive agar supplemented with Escherichia coli was used for the cultivation of Free-Living ‎Amoebae‎. The rate of contamination of water in current study recorded as higher rate with Giardia lamblia 13,2 % followed by Entamoeba histolytica 11,6 %, while Entamoeba coli and Ascaris lumbricoides recorded 5,6 %, then both Enterobius vermicularis and Cryptosporidium spp. found in rate of 4%, the lowest rate of contamination found by free living amoeba Naegleria fowleri and Acanthamoeba. These findings underscore the urgent need for improved water quality management in the Amedi district. Policy recommendations include the implementation of routine water monitoring programs, stricter regulations on agricultural waste disposal, and investment in modernized water infrastructure to prevent contamination through pipe cracks and leaks. Additionally, community health education campaigns should be promoted to raise awareness about waterborne parasitic infections. Strengthening intersectoral collaboration between public health authorities, environmental agencies, and local governments is critical to ensuring a sustainable and safe water supply.